The dynamic relationship between pathological migrating teeth and periodontal disease - Surekha R Rathod; Abhay P Kolte; Snehal Chintawar (Wolters Kluwer Medknow Publications, 2013)
Background: Pathologic migration is defined as change in tooth position resulting from disruption of the forces that maintain teeth in normal position in relation to their arch. The disruption of equilibrium in tooth position may be caused by several etiologic factors. So, the aim of the study was to evaluate the pathologic tooth migration (PTM) in the upper anterior sextant and its relationship with predisposing and external factors such as bone loss, tooth loss, gingival inflammation, age, parafunctions, lingual interposition in the tongue thrust, and oral habits. Aim: The aim of the study was to evaluate the PTM in the upper anterior sextant and its relationship with predisposing and external factors such as bone loss, tooth loss, gingival inflammation, age, parafunctions, lingual interposition in the tongue thrust, and oral habits. Materials and Methods: The study sample consisted of 100 subjects of both sexes, with age ranging from 19 to 72 years. The probing pocket depth and gingival index were recorded for each patient. Competency of lips was also evaluated as competent or incompetent. Habits such as tongue thrusting, nail biting, and lip sucking were evaluated in relation to pathological migration of the tooth. Results: The results showed that no single factor by itself is clearly associated with PTM. As bone loss increases, the association of PTM with additional factors such as tooth loss and gingival inflammation increases. Conclusion: Further studies would be of great help to identify under which circumstances PTM is reversible according to the influence of gingival inflammation, malocclusion, and other factors. This information would contribute to a better understanding of some biological implications of the so-called minor tooth movement.